Transmission of Antimicrobial Resistant Yersinia pestis During a Pneumonic Plague Outbreak. (9th July 2021) - Andrianaivoarimanana, Voahangy; Wagner, David M; Birdsell, Dawn N; Nikolay, Birgit; Rakotoarimanana, Faniry; Randriantseheno, Lovasoa N; Vogler, Amy J; Sahl, Jason W; Hall, Carina M; Somprasong, Nawarat; Cauchemez, Simon; Schweizer, Herbert P; et al.
Abstract: Background: Pneumonic plague (PP), caused by Yersinia pestis, is the most feared clinical form of plague due to its rapid lethality and potential to cause outbreaks. PP outbreaks are now rare due to antimicrobial therapy. Methods: A PP outbreak in Madagascar involving transmission of a Y. pestis strain resistant to streptomycin, the current recommended first-line treatment in Madagascar, was retrospectively characterized using epidemiology, clinical diagnostics, molecular characterization, and animal studies. Results: The outbreak occurred in February 2013 in the Faratsiho district of Madagascar and involved 22 cases, including 3 untreated fatalities. The 19 other cases participated in funeral practices for the fatal cases and fully recovered after combination antimicrobial therapy: intramuscular streptomycin followed by oral co-trimoxazole. The Y. pestis strain that circulated during this outbreak is resistant to streptomycin resulting from a spontaneous point mutation in the 30S ribosomal protein S12 ( rpsL ) gene. This same mutation causes streptomycin resistance in 2 unrelated Y. pestis strains, one isolated from a fatal PP case in a different region of Madagascar in 1987 and another isolated from a fatal PP case in China in 1996, documenting this mutation has occurred independently at least 3 times in Y. pestis . Laboratory experiments revealed this mutation has no detectable impact on fitness or virulence, and revertants to wild-type are rare in other species containing it, suggesting Y. pestis strains containing it could persist in the environment. Conclusions: Unique antimicrobial resistant (AMR) strains of Y. pestis continue to arise in Madagascar and can be transmitted during PP outbreaks. Abstract : A pneumonic plague outbreak in Madagascar involving 22 cases was associated with traditional funeral practices. Retrospective analyses determined that an antimicrobial resistant strain of Yersinia pestis, resistant to streptomycin, was transmitted during this outbreak.